Separation methods in the pharmaceutical industry - Mohd. Setapar, Siti Hamidah (Penerbit UTM, 2007)
It has been discussed in many papers that the development of efficient methods for the separation of bioproducts from fermentation broths is crucial to advancements in biotechnology. Various forms of chromatography and electrophoresis are usefully applied in the purification of high value pharmaceuticals but are expensive and difficult to scale-up beyond laboratory sizes (Cascaval et al., 2001). Therefore, there is a significant need for efficient methods that can separate and concentrate pharmaceutical products continuously, with new cost-effective and simple separation techniques that can be scaled-up easily. For a wide range of chemical and biochemical products, the cost of separation and purification processes represents a significant proportion of the unit cost of production (Tessier et al., 2005, Soto et al., 2005), as well as the contribution of the process to the final cost being of 20.6% to 90% (Cascaval et al., 2001).